A temperature reversal within the rapid Younger Dryas-Holocene warming in the North Atlantic?. (1st December 2016) - Vincent, Jessie H.; Cwynar, Les C.
Abstract: The onset of the Holocene has been generally considered rapid and uninterrupted in the circum-Atlantic region. Loss-on-ignition (LOI – an index of organic carbon) profiles from 18 lateglacial-aged lakes in Nova Scotia, Canada, together with chironomid-inferred temperature reconstructions at 5 sites, demonstrate that the rapid warming from the Younger Dryas (GS-1) to the Holocene was interrupted by a cooling of 1.6–6.4 °C in summer surface lake water temperature. The resulting inflection or reversal on the rising temperature curve has also been identified at 35 sites outside Nova Scotia from terrestrial and marine settings, indicating that this cool step is a robust feature throughout the North Atlantic and is likely the result of major oceanic and atmospheric reorganization of the Holocene climate system. Highlights: A decadal-scale cold reversal occurred in Nova Scotia during the Younger Dryas/Holocene warming. A similar reversal appears at 35 sites throughout the North Atlantic and beyond. Temperature reversals may be a typical feature of rapid climate warming.